The cloud book : how to understand the skies - Hamblyn, Richard, 1965- (Cincinnati, OH : David and Charles, 2008)
A series of illustrated photographs and diagrams that identify and describe various cloud formations and types, the atmospheric conditions that create them, and how they determine weather.
"Met Office.".
Includes bibliographical references (p. 156) and index.
Adult
Keywords: Clouds; Clouds